Injectable In Situ Self-Cross-Linking Hydrogels Based on Hemoglobin, Carbon Quantum Dots, and Sodium Alginate for Real-Time Detection of Wound Bacterial Infection and Efficient Postoperative Prevention of Tumor Recurrence - Zhang, Qicheng (Langmuir : the ACS journal of surfaces and colloids, 2020)
Postoperative wound repair of solid tumors resection, which is afflicted by the complex tumor microenvironment (TME) and associated with the bacterial infection, is worsening and demands prompt solutions. Meanwhile, the tumor recurrence is frequently seen during the subsequent treatment due to intraoperative bleeding. For effective postoperative cancer therapy, nanoscale carriers occur as innovative and sensitive tools for monitoring the wound state, avoiding bacterial infection, and restraining tumor recurrence. Herein, a multifunctional sodium alginate (SA) hydrogel immobilizing hemoglobin (Hb) and pH-sensitive fluorescent changing carbon quantum dots (CQDs) is rationally designed. The multifunctionalization of obtained alginatehemoglobin@CQDs hydrogel (SA@Hb@CQDs) simultaneously consists of detection, hemostasis, and chemodynamic therapy (CDT) with monitoring of wound pH based on CQDs, stanching triggered from SA hydrogel, and Fenton reaction induced by Hb. We demonstrated that SA@Hb@CQDs can stop bleeding quickly, collect wound status information in real-time, and avert bacterial infection as well as inhibit local tumor recurrence effectively. Therefore, our work provides a promising combination approach for postoperative tumor therapy